2009
DOI: 10.1371/journal.pone.0005609
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Endogenous Ligand Bound to a Native Orphan Nuclear Receptor

Abstract: Orphan nuclear receptors have been instrumental in identifying novel signaling pathways and therapeutic targets. However, identification of ligands for these receptors has often been based on random compound screens or other biased approaches. As a result, it remains unclear in many cases if the reported ligands are the true endogenous ligands, – i.e., the ligand that is bound to the receptor in an unperturbed in vivo setting. Technical limitations have limited our ability to identify ligands based on this rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
180
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(185 citation statements)
references
References 65 publications
4
180
1
Order By: Relevance
“…More recently, it has been shown that exogenously expressed HNF4␣ in COS-7 cells binds to LA, and this binding is exchangeable. However, LA does not exhibit a significant effect on the HNF4␣ transcriptional activity (8). In the present study, we showed that luteolin is capable of binding to HNF4␣ and that the binding pocket of HNF4␣ occupied by luteolin is far from that occupied by the fatty acid.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…More recently, it has been shown that exogenously expressed HNF4␣ in COS-7 cells binds to LA, and this binding is exchangeable. However, LA does not exhibit a significant effect on the HNF4␣ transcriptional activity (8). In the present study, we showed that luteolin is capable of binding to HNF4␣ and that the binding pocket of HNF4␣ occupied by luteolin is far from that occupied by the fatty acid.…”
Section: Discussioncontrasting
confidence: 47%
“…Recently, linoleic acid (LA) was identified as an endogenous ligand for HNF4␣; however, the binding of LA to HNF4␣ does not affect its transcriptional activity (8). More recently, small synthetic molecules, such as BIM5078 and BI6015, were identified as antagonists for HNF4␣.…”
mentioning
confidence: 99%
“…Another facet of HNF4A biology that remains unresolved is the identity of its endogenous ligand(s). Although historically considered an orphan nuclear receptor, several fatty acids (FA), including linoleic acid, have been identified as ligands for HNF4A (Hertz et al 1998;Palanker et al 2009;Yuan et al 2009). Fatty acids are an attractive class of putative regulators of HNF4A, since the microbiota are known to regulate FA absorption in zebrafish IECs (Semova et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Originally designated as an orphan member due to the lack of a known ligand, subsequent studies have identified fatty acids bound in the ligand binding pocket with linoleic acid as the potential endogenous HNF4␣ ligand (5)(6)(7)(8). HNF4␣ is critical for proper hepatic lipid homeostasis, as evidenced by the development of steatosis in Hnf4␣-deficient mouse livers (9).…”
mentioning
confidence: 99%